2021
DOI: 10.1042/cs20201239
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for brain renin–angiotensin system activation during DOCA-salt hypertension

Abstract: Brain renin–angiotensin system (RAS) activation is thought to mediate deoxycorticosterone acetate (DOCA)-salt hypertension, an animal model for human primary hyperaldosteronism. Here, we determined whether brainstem angiotensin II is generated from locally synthesized angiotensinogen and mediates DOCA-salt hypertension. To this end, chronic DOCA-salt-hypertensive rats were treated with liver-directed siRNA targeted to angiotensinogen, the angiotensin II type 1 receptor antagonist valsartan, or the mineralocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 44 publications
2
46
1
Order By: Relevance
“…In this sense, the source of brain Ang II could be represented by circulating Ang II that binds to brain Ang receptors in conditions where the BBB integrity is compromised, such as deoxycorticosterone acetate (DOCA)-salt hypertension. It has been shown that DOCA-salt suppressed plasma and brain Ang II in parallel, while spironolactone simultaneously increased Ang II and lowered blood pressure, indicating that DOCA-salt hypertension is not mediated by brain RAS activation [49]. Contrary to this hypothesis, we have shown that Ang II levels were increased in brainstem neurons from SHRs compared with those from WKY animals.…”
Section: The Ras System In the Braincontrasting
confidence: 98%
“…In this sense, the source of brain Ang II could be represented by circulating Ang II that binds to brain Ang receptors in conditions where the BBB integrity is compromised, such as deoxycorticosterone acetate (DOCA)-salt hypertension. It has been shown that DOCA-salt suppressed plasma and brain Ang II in parallel, while spironolactone simultaneously increased Ang II and lowered blood pressure, indicating that DOCA-salt hypertension is not mediated by brain RAS activation [49]. Contrary to this hypothesis, we have shown that Ang II levels were increased in brainstem neurons from SHRs compared with those from WKY animals.…”
Section: The Ras System In the Braincontrasting
confidence: 98%
“…GFR in healthy SD rats is 1.0±0.04 mL/min per 100 g of body weight. 23 At 5 weeks after the 5/6th Nx procedure, GFR had decreased to 0.38±0.10 mL/min per 100 g of body weight. Neither vehicle nor any treatment affected GFR over the next 4 weeks (Figure 4A).…”
Section: Agt Sirna Is Renoprotectivementioning
confidence: 91%
“…In renal tissue, AGT was quantified by Western blotting and normalized versus GAPDH as described before. 23 Plasma renin concentration (PRC) was measured by quantifying Ang I generation in the presence of excess porcine AGT (detection limit, 0.17 ng Ang I/mL per hour). 24 Ang I was measured by radioimmunoassay.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Indeed, in the present study angiotensins could not be detected in brain tissue without angiotensinogen overexpression, and previous studies even suggested that the small amounts of Ang II that could be detected in the brain are derived from blood, i.e. they do not represent local Ang II synthesis in the brain [7,13]. An important next step would therefore be to demonstrate that tonin-driven brain angiotensinogen cleavage truly has in-vivo relevance in either normal physiology or pathology.…”
Section: In Micementioning
confidence: 43%
“…DOCA-salt treatment will lower circulating RAS activity, and thus a simultaneous up-regulation of the brain RAS would be an indication of a fully independent RAS. Yet, disappointingly, a recent study that used small interfering RNA (siRNA) to selectively silence hepatic angiotensinogen showed that eliminating circulating angiotensinogen also made brain Ang II disappear in the DOCA-salt model [13]. In other words, brain Ang II in this model still relied on hepatic angiotensinogen, and most likely represented Ang II taken up from blood.…”
Section: In Micementioning
confidence: 99%